An Unusual Texture Evolution in Extruded Mg–14Gd–Based Alloy during Annealing. Issue 4 (13th February 2018) - Li, Rongguang; Zhang, Jinghuai; Fu, Guangyan; Zong, Lin; Guo, Beitao; Yu, Yongmei; Guo, Shuguo
Abstract : Texture evolution during annealing in various wrought Mg alloys is still controversial and texture control is an effective way of reducing mechanical anisotropy and improving secondary formability for Mg alloys. In this study, the electron backscattered diffraction (EBSD) method is used to monitor the texture evolution during the annealing process of a Mg–14Gd–2Ag–0.5Zr extruded bar. The novel phenomenon, that is, the texture evolution from <0001>⊥ED to <0001> ||ED, or rather, the increase fraction of grains with <0001> ||ED accompanied by the decrease fraction of grains with <0001>⊥ED, is found and discussed in the high‐RE containing Mg alloy for the first time. The effect factors, stored energy in different textured grains and grain boundary misorientation, are mentioned to analyze the texture evolution. Abstract : The weak <10‐10>||ED texture of extruded high‐RE containing Mg alloy evolves into an unusual <0001>||ED texture during annealing. The evolution accompanied with the increased fraction of <0001>||ED grains and the decreased fraction of <0001>⊥ED grains is mainly related to the different stored energy and the grain boundary misorientation.